The Role of Supportive Leadership and Achievement Motivation in Fostering Teachers’ Innovative Behaviors: A Literature Reviews - Utami, Batina Yulia; Hadiyanto, Hadiyanto; Rifma, Rifma; Susanti, Lusi (Postgraduate School, Universitas Negeri Padang, 2024)
This study aims to analyze the influence of principals' supportive leadership and teachers' achievement motivation on the innovative behaviors of teachers at Junior High School (JHS) IV Jurai, Pesisir Selatan Regency. A library research methodology was employed to systematically analyze data from scholarly sources such as peer-reviewed journals and academic books. The findings reveal that supportive leadership by principals, characterized by trust-building, constructive feedback, and encouragement of experimentation, creates an environment conducive to innovation. Simultaneously, teachers with high achievement motivation demonstrate a proactive drive to adopt new teaching practices, engage in professional development, and collaborate in learning communities, accelerating educational innovation. The synergy between these factors significantly enhances teachers' creativity and positively impacts student learning outcomes. This study concludes that fostering innovation in schools requires an integrated approach that empowers principals through leadership training and supports teachers with comprehensive professional development programs. Such initiatives can promote a positive school climate, align organizational goals with teacher motivation, and sustain long-term educational advancements.